(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Rapid urbanization, industrial growth, and increasing water scarcity have intensified the need for advanced wastewater treatment technologies. Modern treatment approaches focus on higher purification efficiency, energy saving, resource recovery, and environmental sustainability. This article reviews current development trends in wastewater treatment, including membrane technologies, biological nutrient removal, advanced oxidation processes, digital monitoring, and circular economy principles. The analysis shows that integration of innovative technologies significantly improves treatment performance while reducing operational costs and ecological impact. These trends are particularly important for regions with limited water resources and growing environmental pressures.